2016
DOI: 10.1073/pnas.1506903113
|View full text |Cite
|
Sign up to set email alerts
|

Central auditory neurons have composite receptive fields

Abstract: High-level neurons processing complex, behaviorally relevant signals are sensitive to conjunctions of features. Characterizing the receptive fields of such neurons is difficult with standard statistical tools, however, and the principles governing their organization remain poorly understood. Here, we demonstrate multiple distinct receptivefield features in individual high-level auditory neurons in a songbird, European starling, in response to natural vocal signals (songs). We then show that receptive fields wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(100 citation statements)
references
References 33 publications
3
93
4
Order By: Relevance
“…Another recent avian forebrain study [54] used a maximum noise entropy (MNE) approach to uncover multiple receptive fields sensitive to second-order aspects of the stimulus. Unlike the above two GNM [24,53] approaches, this model does not have hidden units with sigmoidal nonlinearities, but finds multiple quadratic features.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent avian forebrain study [54] used a maximum noise entropy (MNE) approach to uncover multiple receptive fields sensitive to second-order aspects of the stimulus. Unlike the above two GNM [24,53] approaches, this model does not have hidden units with sigmoidal nonlinearities, but finds multiple quadratic features.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, the same neuronal circuit that can implement Gaussian tuning for selectivity can also implement, by using different parameter values, a MAX-like operation (output = maximum(input)), which is important for invariance and has been observed experimentally in the mammalian visual cortex [102,103] and in the central auditory system of a songbird [104]. The predicted computational flexibility was experimentally verified in the European starling, a species of songbird, where individual central auditory neurons could switch between the MAX-like operation for invariance and a tuning operation for selectivity, depending on the stimulus and network state [104], displaying sparse responses and multidimensional selectivity [105].A Gaussian tuning function is also useful for generalization after training on a limited data set. Specifically, radial Gaussian basis functions are smooth and interpolate well from training data to new data [106].…”
mentioning
confidence: 67%
“…1E). Suppressive features have been observed in visual cortex (Rust et al, 2005, Chen et al, 2007), though rarely in the auditory system (though see (Harper et al, 2016, Kozlov and Gentner, 2016). For the neuron in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the first, the MNE analysis was applied to neurons in a secondary auditory cortex-like center in the songbird (Kozlov and Gentner, 2016). In concord with our results, the authors found multiple excitatory and suppressive features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation